"Under His Eye": Religious Appropriation and American Civil Religion in Hulu's The Handmaid's Tale. Issue 2 (3rd April 2022) - Engstrom, Erika; Stephenson, David; Kim, Yung Soo; Valenzano, Joseph M.
ABSTRACT: This study explores how the Hulu streaming series The Handmaid's Tale (2017-) extends Margaret Atwood's novel by depicting the aftermath of the transformation of the United States by the fake theocracy of Gilead through visual cues that evoke American civil religion, a performative system of symbols and rituals that reifies national values and unites a pluralistic society. A textual analysis of the episode "Household, " set in Gilead's capital of a reimaged Washington, D.C., found four main themes regarding the onscreen depiction of Gileadean theocracy and its surface victory over the United States and its accompanying symbols of American civil religion: (a) religion used as a façade, (b) desecration of sacred sites in American civil religion, (c) silencing, and (d) surveillance. This study adds a unique contribution to the study of American civil religion through its examination of visual images in a fictional televisual text.